Plasma homocysteine and aminothiol levels in idiopathic epilepsy patients receiving antiepileptic drugs - YALÇIN, AHMET SUHA (WALTER DE GRUYTER GMBH, 2019)
Objective: Homocysteine is a sulfur containing amino acid that is formed during methionine metabolism. Patients under long-term antiepileptic drug treatment often have hyperhomocysteinemia. These patients have low levels of serum folate, vitamin B12 and vitamin B6, all of which are associated with homocysteine metabolism. We have investigated the effects of valproic acid and new generation antiepileptic drugs (lamotrigine and levetiracetam) on plasma levels of homocysteine and aminothiols as well as serum vitamin B12 and folic acid. Materials and methods: Forty-seven idiopathic epileptic patients on antiepileptic drugs were compared with 38 age-matched healthy controls. Commercial immuno-assay methods were used for vitamin B12 and folic acid analyses. Homocysteine, cysteine, cysteinylglycine and glutathione levels were determined by high performance liquid chromatography. Results: There was no significant difference in patient and control values in terms of vitamin B12, folic acid and homocysteine. Valproic acid and lamotrigine seemed to effect aminothiol redox status. Glutathione levels of epileptic patients receiving valproic acid and lamotrigine were higher than controls. Conclusion: Our results suggest that redox homeostasis may be impaired and glutathione synthesis increased in response to the oxidative stress caused by antiepileptic drug use.
Keywords: Antiepileptic drugs; Vitamin B12; Folic acid; Homocysteine; Glutathione; Idiopathic epilepsy patients; FOLIC-ACID; SODIUM VALPROATE; SERUM-LEVELS; FOLATE; CARBAMAZEPINE; PHENYTOIN; VITAMIN-B-12; MONOTHERAPY; HYPERHOMOCYSTEINEMIA; METABOLISM